2010
DOI: 10.1590/s1517-86922010000500009
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos da dieta suplementada com ômega-3 no músculo sóleo de ratos submetidos à natação: análise histológica e morfométrica

Abstract: RESUMOAs lesões musculares têm sido observadas como as mais frequentes nos esportes. Considerando a produção de espécies reativas de oxigênio como um fator de risco para instalação de lesões e características antioxidantes e anti-inflamatórias do ômega-3, o objetivo deste trabalho foi verificar as alterações histológicas e morfométricas do músculo sóleo de ratos que realizaram natação, associado a uma dieta suplementada com ômega-3. Para sua realização foram utilizados 31 ratos Wistar divididos em quatro grupo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Histological patterns of muscle damage were observed in the specimens from animals that trained without fish oil supplementation. In that study, the authors pointed out that the use of fish oil had a protective effect against muscular injuries [31]. In the same way, despite the use of different techniques, our study observed intense edema, neutrophilic inflammation and foci of necrosis in groups that performed resistance exercise and did not take fish oil.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Histological patterns of muscle damage were observed in the specimens from animals that trained without fish oil supplementation. In that study, the authors pointed out that the use of fish oil had a protective effect against muscular injuries [31]. In the same way, despite the use of different techniques, our study observed intense edema, neutrophilic inflammation and foci of necrosis in groups that performed resistance exercise and did not take fish oil.…”
Section: Discussionsupporting
confidence: 72%
“…Different from our experimental exercise model, Garcia et al [31] submitted rats for 28 days to continuous aerobic training with an overload of 5% of body weight and supplemented with fish oil. Histological analyzes of the soleus muscle of the animals supplemented with fish oil showed that the fibers had no increase in endomysial tissue, peripheral nuclei with reduced phagocytosis, and less pronounced polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…The animals of the exercise groups (G2 and G4) were subjected to 20 swimming sessions over a period of four weeks, Mondays to Fridays, between 1 pm and 5:30 pm, in two tanks containing water at 30ºC. The training program consisted of daily swimming sessions, five days per week (Garcia et al, 2010). In the first week, to adapt them to the exercise, the animals swam for 10, 20, 30, 40, and 50 minutes a day.…”
Section: Exercise Protocolmentioning
confidence: 99%
“…Moreover, iGF-1 plays an important role in the prevention of muscular atrophy, since in response to injuries, the satellite cells stimulate increase of the iGF synthesis, leading them to proliferation and differentiation, forming myoblasts which blend to generate new fibers 29 . A study developed by Garcia et al 30 , using training methodology similar to in this investigation, presented in the morphometric analysis of soleus of rats submitted to daily training that, after it, some muscle fibers presented initial and complete stages of the phagocytosis process, angular fibers, atrophic, centered nuclei and sarcolemma loss, which indicate the onset of degeneration. Although an analysis at the cellular level has not been done in this study, it is possible that it had occurred after the proposed training, added to the damage derived from the nervous comprehension.…”
Section: Discussionmentioning
confidence: 90%